Performing place: natural landscape, cultural place, performances of Sri Lankan traditional settlements: Kandy and Lankathilaka - De Silva, Wasana (2014)
Traditional settlement patterns in Sri Lanka reflect a sense of harmony between built forms, architecture and their natural landscape context. In contrast to this, many new developments neglect or overpower natural landscape features. In traditional societies a range of sites are celebrated through the performance of ritual activities which create significant distinctive places and dwelling patterns. This research focuses on traditional settlements of Sri Lanka to examine emerging architecture and built space, focusing on the relationships between natural landscape, cultural place and the role of ritual and performance. A number of pilot case studies followed by an in depth comparative case study of a city and a village - Kandy and Lankathilaka respectively - address the topic by examining how common narratives perform in contrasting landscape locations. The thesis develops the theoretical concept of the ‘Performative phenomenon’ as a means of understanding the dynamic nature of cultural place and landscape in the Sri Lankan context. A theoretical framework and case study method is established by combining aspects of phenomenology, anthropology, psychology, ethnography, landscape theory, and architectural interpretation. A wide range of literature review draws on key concepts such as chora and topos, dwelling, ideal forms, Mitte and actor-network-theory to theorise how ‘place’ emerges through cultural practices in space and time. Fieldwork and archival research provide detailed evidence of site specific practices, most notably in the Asala perahera festivals which are repeated at both case study locations. A pattern matching technique is applied for analysing data, presented in tables, diagrams, maps and illustrations. In both case studies, the experience of ideal forms and dwelling is evident throughout the performing process of Asala perahera. Place is produced by repeated events, such as, parading, marking geometrical patterns, sound performing, narrating, body performing and so on, producing and sustaining an inter-related network of performers and landscape. It is concluded that Kandy city is experienced as an ‘inside’ enclosed within three mountains, while Lankathilaka village is experienced as a divine centre. Through locally specific performative processes, common ideal forms continue to flourish, shaped by the natural landscape and architecture, which reflect the chora of the place.